2020
DOI: 10.7150/ijms.51126
|View full text |Cite
|
Sign up to set email alerts
|

The effect of CCL5 on the immune cells infiltration and the prognosis of patients with kidney renal clear cell carcinoma

Abstract: Background: Kidney renal clear cell carcinoma (KIRC) is the most representative subtype of renal cancer. Immune infiltration was associated with the survival time of patients with tumors. C-C chemokine ligand 5 (CCL5) can promote the malignant process of tumor and be related to infiltration immune cells in some cancers, but not reported in KIRC. Methods: The expression profile and clinical data were obtained from The Cancer Genome Atlas (TCGA) database. The correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“… 47 At the same time, CCL5 and CXCL13 have been shown to be potential biomarkers and therapeutic targets, which is related to CD8+ T cell infiltration in KIRC. 46 , 48 The chemokine XCL2 was recently shown to play a critical role in recruiting cross-presenting dendritic cells to tumors. 49 In addition, studies have reported that tumor-resident natural killer cells express many chemokine genes (such as CCL4, CCL5, and XCL2), which are important for the infiltration of dendritic cells, T cells, and other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“… 47 At the same time, CCL5 and CXCL13 have been shown to be potential biomarkers and therapeutic targets, which is related to CD8+ T cell infiltration in KIRC. 46 , 48 The chemokine XCL2 was recently shown to play a critical role in recruiting cross-presenting dendritic cells to tumors. 49 In addition, studies have reported that tumor-resident natural killer cells express many chemokine genes (such as CCL4, CCL5, and XCL2), which are important for the infiltration of dendritic cells, T cells, and other immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Ccl5 expression was reduced by aPD1/ADA gel and aPD1 gel (2.2-fold and 3.9-fold) in relative to saline. Elevated Ccl5 expression was associated with cancer-related inflammation in RCC cell lines and poor clinical prognosis in patients with RCC ( Gelbrich et al, 2017 ; Bai et al, 2020 ). Bai et al described pathways in which high Ccl5 expression resulted in recruitment of tumor-infiltrating Tregs, which correlated with poor overall survival ( Bai et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated Ccl5 expression was associated with cancer-related inflammation in RCC cell lines and poor clinical prognosis in patients with RCC ( Gelbrich et al, 2017 ; Bai et al, 2020 ). Bai et al described pathways in which high Ccl5 expression resulted in recruitment of tumor-infiltrating Tregs, which correlated with poor overall survival ( Bai et al, 2020 ). Ccl5 -deficiency mice had increased CD8 + T cells in tumors and reversal of aPD1 resistance in a colorectal cancer model ( Zhang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other immune signatures revealed that CCL5 expression significantly increased the scores of 10 immune cells (Macrophages, NK cells, CD8 + T cells, CAFs, Treg, CD4 + regulatory T cells, MDSC, TAM, B cells, and Th17), while lncRNA UCA1 significantly decreased the scores of TAM, MDSC, and M2 macrophages. CCL5 is secreted by T cells, Platelets, Macrophages, Endothelial cells, and Fibroblasts and stimulates the migration of T cells and monocytes to drive apoptosis of tumor-infiltrating T cells; therefore, it was found that reducing the expression of CCL5 may have a beneficial effect on various tumors (Bai et al, 2020;Korbecki et al, 2020;Nakamura et al, 2021). Besides, there are very limited studies on the involvement of lncRNA UCA1 in tumor immunity, among which studies found that lncRNA UCA1 as an oncogene could suppress the host immune system by up-regulating the PDL1 level in gastric cancer cells (Wang J.-D. et al, 2019).…”
Section: Discussionmentioning
confidence: 99%